Peculiarities of nonadditive changes in conductivity of nano-PDLC under influence of magnetite and single-wall carbon nanotubes - Kopčanský, P.; Timko, M.; Mitrova, Z.; Tomašovičová, N.; Tomčo, L.; Kovalchuk, O.V.; Kovalchuk, T.M.; Oleinikova, I.V.; Lad, A.I.; Studenyak, I.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Studied in this work has been the effect of nanoparticles – magnetite and
single-wall carbon nanotubes – separately and together on the conductivity of nematic
liquid crystal 6CHBT dispersed in polyvinyl alcohol. Morphology of these films was
analyzed using an electron microscope. When using selected technologyof homogenizing
the mixture components, there takes place formation of liquid crystals dispersed in the
polymer matrix with the average sizes of liquid-crystal droplets close to 500 nm (nanoPDLC).
It has been found that simultaneous introduction of magnetite and nanotubes
results in lowering the conductivity of nano-PDLC as compared to the total conductivity
of nano-PDLC with each kind of nanoparticles separately. It has been suggested that the
main mechanism of this effect lies in formation of deep centers for electron capture by
complexes with different types of nanoparticles, which leads to a decrease in electronic
conductivity through the polymer matrix.